Non-typhoidal Salmonella bloodstream infections in Kisantu, DR Congo: Emergence of O5-negative Salmonella Typhimurium and extensive drug resistance. - Bieke Tack; Marie-France Phoba; Barbara Barbé; Lisette M Kalonji; Liselotte Hardy; Sandra Van Puyvelde; Brecht Ingelbeen; Dadi Falay; Dauly Ngonda; Marianne A B van der Sande; Stijn Deborggraeve; Jan Jacobs; et al. (PLOS Neglected Tropical Diseases, 2020)
Background Non-typhoidal Salmonella (NTS) are a major cause of bloodstream infection (BSI) in sub-Saharan Africa. This study aimed to assess its longitudinal evolution as cause of BSI, its serotype distribution and its antibiotic resistance pattern in Kisantu, DR Congo. Methods As part of a national surveillance network, blood cultures were sampled in patients with suspected BSI admitted to Kisantu referral hospital from 2015-2017. Blood cultures were worked-up according to international standards. Results were compared to similar data from 2007 onwards. Results In 2015-2017, NTS (n = 896) represented the primary cause of BSI. NTS were isolated from 7.6% of 11,764 suspected and 65.4% of 1371 confirmed BSI. In children <5 years, NTS accounted for 9.6% of suspected BSI. These data were in line with data from previous surveillance periods, except for the proportion of confirmed BSI, which was lower in previous surveillance periods. Salmonella Typhimurium accounted for 63.1% of NTS BSI and Salmonella Enteritidis for 36.4%. Of all Salmonella Typhimurium, 36.9% did not express the O5-antigen (i.e. variant Copenhagen). O5-negative Salmonella Typhimurium were rare before 2013, but increased gradually from then onwards. Multidrug resistance was observed in 87.4% of 864 NTS isolates, decreased ciprofloxacin susceptibility in 7.3%, ceftriaxone resistance in 15.7% and azithromycin resistance in 14.9%. A total of 14.2% of NTS isolates, that were all Salmonella Typhimurium, were multidrug resistant and ceftriaxone and azithromycin co-resistant. These Salmonella isolates were called extensively drug resistant. Compared to previous surveillance periods, proportions of NTS isolates with resistance to ceftriaxone and azithromycin and decreased ciprofloxacin susceptibility increased. Conclusion As in previous surveillance periods, NTS ranked first as the cause of BSI in children. The emergence of O5-negative Salmonella Typhimurium needs to be considered in the light of vaccine development. The high proportions of antibiotic ...